Psychological characteristics, sport engagement, and performance in alpine skiers. (March 2020) - Fawver, B.; Cowan, R.L.; DeCouto, B.S.; Lohse, K.R.; Podlog, L.; Williams, A.M.
Abstract: Previously, investigators have sought to clarify the role of psychological factors in the development of expertise across numerous sport domains; however, almost no empirical work exists on winter sport athletes. Using a retrospective design, we examined associations between psychological traits, engagement in practice-related activities, and performance among sub-elite level, youth alpine skiers. A total of 169 skiers (88 women) enrolled at professional development academies in the United States completed a battery of questionnaires assessing practice history profiles and performance milestones, as well as various psychological factors (e.g., mental toughness, grit, perfectionism). Performance was assessed using national ranking across both speed and technical disciplines. In addition to linear models and MANOVA/MANCOVA tests, linear mixed-effect regressions were utilized to assess relationships between psychological factors, practice hours, and ranking over time. Higher scores on perfectionistic strivings (personal standards) were associated with improved performance. Also, grit was associated with increased engagement in individual practice hours. Coach-led one-on-one practice hours were associated with increased perfectionistic concerns (e.g., parental pressure), while indirect exposure (e.g., attending events without competing) was associated with decreased mental toughness. Findings highlight potentially important associations between athletes' dispositional characteristics, prolonged ski engagement, and performance trajectory. Highlights: Grittier skiers showed greater engagement in individual practice. Personal standards and coach pressure associated with better rank. One-on-one practice associated with greater parental pressure. Competition hours negatively associated with confidence.